Peran Orangtua Terhadap Anak Dalam Mengembangkan Kecerdasan Emosional Dan Spiritual Melalui Pendidikan Islam Berbasis Kisah-Kisah Nabi Di Dalam Al-Qur’an - Siti Rohmah (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This article contructs the role and strategies of parents toward the children to develop the emotional and spiritual intelligence through Islamic education based on the dialogue or communication stories of prophets (Nuh, Ibrahim, Ya’qub and Luqman). It is applied qualitative research and thematic approaches in analyzing verses on parent-children dialogue or communication in the stories of prophets. This article concludes that the role of parents toward the children should be based on the tauhid of Allah and love. Those two engendered the virtues of emotional and spiritual intelligence. The communication or dialogue by the prophets to their children used the certain strategies and methods and also contented the materials to increase the emotional and spiritual intelligence.